A Study of Needs for Instructional Supervision of Early Childhood Teachers in Child Development Centers with Urgent Improvement Need Under the Local Administrative Organization - Punyatiprawadee, Jutharat; Bulpakdi, Buntarika; Akkaraputtapong, Panya (Suan Dusit Graduate School Academic Journal, 2024)
The purpose of this study was to study the current situation, expectations, and analyze the needs for instructional supervision of early childhood teachers in child development centers under the local government organization. The survey research was employed and the sample consisted of 169 child development centers obtained via stratified random sampling. The instrument used for data collection was a questionnaire using a rating scale with an IOC value greater than 0.50. The data analysis included frequency, percentage, mean, standard deviation, and modified priority needs index. It was found that the overall instructional supervision practice of early childhood teachers in the child development center was at the high level. When considering each aspect, it was found that the aspect practiced at the highest level was experience management, followed by environment, media and learning resources management, and development assessment, respectively. The overall expectation of instructional supervision was at the highest level. The most expected aspects were experience management and environment, media and learning resources management, followed by development assessment as well as experience plan preparation, respectively. Regarding the modified priority needs index, the development assessment was the most needed supervision aspect, followed by environment, media and learning resource management and experience plan preparations, respectively.